Modulation of enhancer activity by the hormone responsive regulatory element from mouse mammary tumor virus. - Ostrowski, M C (1984)
Addition of the transcriptional enhancers present in the U3 region of the Harvey murine sarcoma virus (HaMuSV) long terminal repeat (LTR) to recombinant chimeras in which the HaMuSV transforming gene (Ha-v-ras) is expressed from the mouse mammary tumor virus (MMTV) promoter increases the ability of the MMTV v-ras chimeras to transform mouse fibroblasts in culture 50- to 100-fold. Significant stimulation of transfection efficiency occurs only when glucocorticoids are present in the culture medium. Glucocorticoids also elevate the steady-state concentration of MMTV-initiated v-ras mRNA in cell lines isolated from these transfections, and MMTV-v-ras fusion transcripts are initiated at the normal MMTV cap site; potential cryptic initiation events associated with the enhancer could not be detected. The ability of the enhancer to increase the transcriptional activity of the MMTV promoter was also studied in acute transfection assays where expression of the chloramphenical acetyl transferase (CAT) gene is driven by the MMTV promoter. In this system the strong positive effect on MMTV transcription is again obtained only when the cells are hormone treated. These experiments indicate that the hormone-regulatory region is capable of modulating the function of an exogenously introduced enhancer element.